The Typology of the Gayo Traditional House Facade is Reviewed Based on the Context of the form Element Analysis - Purnama Lisa, Nova; Fithra, Herman; Siska, Deassy; Dafrina, Armelia (International Journal of Engineering and Technology, 2019)
The building facade is an important element in the delivery of functions, meanings and a period of culture when the building stands. This study was carried out to dig deeper into the typology of the facade of the traditional Gayo house which is a heritage house of Reje Baluntara. The purpose of this study was to identify and analyze the facade typology of Gayo traditional house buildings in an effort to explore historical data and as a data inventory that would later be useful in developing the scientific treasures of traditional architecture which became the archipelago’s architectural cultural heritage. The typology of facades in the Gayo traditional house was carried out with the aim of: classifying the formation of facade-forming elements, obtaining a dominant formation on each element forming the facade so that it can be found in the traditional Gayo house inherited from Reje Baluntara which still retains its authenticity. In this study, the method used was descriptive-qualitative. The analysis used is by classifying facades based on the shape elements of the facade field, namely the basic field, the wall area and the upper field or roof area. The findings of this study are found that the basic field facade typology which is the base area of the building becomes the most important part, because it relates to the transition to land, so the foundation of the building is the most important element to stand the building, there are 26 columns in a gayo traditional house arranged in a grid 3 meters with an umpak foundation system using large and strong stones. There are not many openings in the facade on the wall, this is done as a context for the temperature of the relatively cold Gayo area. Typology of roof formation is a roof shield that extends and is the main roof. Â Â